Postparetic Synkinesis: Objective and Subjective Comparisons of Depressor Anguli Oris Myectomies versus Depressor Anguli Oris and Buccinator Myectomies - Sanchez, Cristina V.; Ercan, Alp; Rozen, Shai M. (Journal of Reconstructive Microsurgery, 2024)
Background Muscles affected by postparetic synkinesis have imbalanced tonicity that limit perioral mimetic movement and inhibit the ability to smile. The depressor anguli oris (DAO) muscle has been a common myectomy target for the treatment of perioral synkinesis. While addition of buccinator myectomies to DAO myectomies has risen, no studies have analyzed the effects of buccinator myectomies. The goal of this study was to evaluate and compare the effects of a DAO myectomy with and without concomitant buccinator myectomy through objective facial metrics and subjective patient-reported outcomes.Methods This study is a retrospective review of patients with postparetic synkinesis who underwent DAO myectomy (DAO myectomy group) or DAO myectomy with buccinator myectomy (DAO + Buccinator myectomies group). Outcomes included postoperative differences in objective smile measures (smile angle, excursion, and dental show) using validated software and patient-reported outcomes using the Facial Disability Index (FDI) questionnaire and a myectomy-specific questionnaire.Results After chart review, 18 patients were included in the DAO myectomy group and 19 in the DAO + Buccinator myectomies group. There were no significant postoperative differences between the groups in (1) smile excursion, angle, or dental show at resting, closed smile, or open smile (p > 0.05), (2) FDI physical and social scores, p = 0.198 and 0.932, respectively, or (3) myectomy-specific questionnaire responses (p > 0.05).Conclusion The addition of a buccinator myectomy to a DAO myectomy does not provide significant clinical benefit when compared with an isolated DAO myectomy, based on objective measures and subjective patient-reported outcomes.
Keywords: synkinesis; facial paralysis; myectomies